Haptoglobin halts hemoglobin’s havoc - Gregory J. Kato (The Journal of Clinical Investigation, 2009)
Hemoglobin (Hb) is crucial to the function of the red blood cell. However, when it is released during intravascular hemolysis from the cell into blood plasma, it produces a state of NO depletion, oxidant stress, and vascular dysfunction, including hypertension. In their study reported in this issue of the JCI, Boretti and colleagues used canine and guinea pig models to demonstrate that pharmacological doses of glucocorticoid can increase the plasma levels of haptoglobin (Hp), the principal plasma-binding protein for free Hb (see the related article beginning on page 2271). Hp prevented Hb-induced hypertension and the generation of oxidant damage to the kidney. Neutralization of free Hb appears to be part of the downstream antiinflammatory properties of glucocorticoid.